2013
DOI: 10.1111/hpb.12051
|View full text |Cite
|
Sign up to set email alerts
|

Coagulopathy after a liver resection: is it over diagnosed and over treated?

Abstract: In spite of an elevation in PT-INR, patients undergoing a liver resection demonstrated a brief hypercoagulable state, followed by normal coagulation function based on TEG. These data call into question the practice of utilizing PT-INR to guide plasma transfusion and timing of prophylactic anticoagulation after a liver resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
41
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 20 publications
(30 reference statements)
7
41
1
2
Order By: Relevance
“…These findings are similar to those reported by other groups [21,24,31]. It is now recognised that conventional coagulation tests have many limitations, in that they are insensitive to endogenous anticoagulant levels and give no information on the presence or absence of hypercoagulability [32].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are similar to those reported by other groups [21,24,31]. It is now recognised that conventional coagulation tests have many limitations, in that they are insensitive to endogenous anticoagulant levels and give no information on the presence or absence of hypercoagulability [32].…”
Section: Discussionsupporting
confidence: 90%
“…That these changes are specific to hepatic resection, and are not mirrored by other abdominal surgery, has been demonstrated in a number of other studies [21,22,30,31]. Following other types of major surgery, there is a small (20%) initial reduction in pro-and anticoagulant levels up to day 2, and only modest increases in VWF and factor VIII [30].…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have shown that increased values of these parameters accurately predicted liver-related death and occurrence of severe complications after hepatectomy [18,19]. Several previous reports have identified the following risk factors for elevated serum bilirubin and INR after hepatic resection: advanced age, underlying hepatic steatosis, significant intraoperative blood loss, and prolonged operation time [17,[20][21][22]. However, it is difficult to accurately interpret these results because the patient populations in these analyses have been heterogeneous, and have included healthy living liver donors and patients with benign liver diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Serum bilirubin and international normalized ratio (INR) are well-known indices of liver function [14][15][16][17]. Previous studies have shown that increased values of these parameters accurately predicted liver-related death and occurrence of severe complications after hepatectomy [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…10,11 However, our laboratory has used thromboelastography (TEG) to show that a hypercoagulable state exists following liver resection. 12,13 This test uses whole blood to provide a comprehensive assessment of the coagulation profile.…”
mentioning
confidence: 99%